2010
DOI: 10.1111/j.1464-410x.2010.09271.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo microwave‐induced porcine kidney thermoablation: results and perspectives from a pilot study of a new probe

Abstract: thermoablations overall. The kidneys were then surgically removed, and necrotic lesions measured and evaluated microscopically. The sphericity index (SI) was also calculated to evaluate lesion reproducibility. Areas of renal tissue that were missed were then microscopically evaluated by NADH in vivo staining. RESULTSIn all, 32 thermoablations were applied; the mean ( SD ) lesion diameter ranged from 1.2 (0.3) to 4.2 (0.1) cm and changed in relation to both power and time of exposure. The 50-W power particularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…The mean age-adjusted Charlson comorbidity index was 4.8 (range, 3-7). The mean RENAL score was 9.4 (range, [8][9][10][11][12]. Table I shows the clinical and laboratory characteristics of enrolled patients.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The mean age-adjusted Charlson comorbidity index was 4.8 (range, 3-7). The mean RENAL score was 9.4 (range, [8][9][10][11][12]. Table I shows the clinical and laboratory characteristics of enrolled patients.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study on porcine kidney (8) demonstrated that a standardized method of microwave administration could be obtained by using pre-determined independent variables such as power of treatment and time of exposure to energy. The Amica-probe antenna is a new refrigerated probe able to determine approximately spherical lesions with a maximum of 2.7±0.3 cm in the animal kidney tissue by an exposure time of 5 min and 50 W power (8). The best results could be obtained by using 15 min of time exposure and 50 W power with induced-lesion SI ~1.0 and diameters from 4.1 to 4.2 cm (±0.1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations